Choosing a Surgical Access Point for Hysterectomy: A Paradigm Shift Over a 10-Year Span - Ebner, Florian; de Gregorio, Niko; Lato, Christiane; Ohly, Valerie; Janni, Wolfgang; Spohrs, Jennifer; Jerg-Bretzke, Lucia; Walter, Steffen (Frontiers in Medicine, 2020)
Background: When choosing a surgical procedure for a hysterectomy, doctors and patients have various possibilities due to the multiple surgical accesses. Aim of this study was to descriptively analyse the development of the past 10 years at Ulm University Hospital and to assess and control variables that were significantly affected by the surgical method, and for potential variables that may significantly influence these surgical access routes as well as. Material and Methods: This monocentric study retrospectively assessed the data from all patients who underwent a hysterectomy due to a benign disease or endometrial cancer from January 2007 until December 2016. Results: When considering the benign indications, myomas and descensus genitalis occurred most frequently (49.5% and 30.6%). The percentage of abdominal procedures declined from 2007 until 2016 from 61.4% to 13.4% for all hysterectomies, while it increased from 4.1% to 69.7% for laparoscopic hysterectomies. The rate of vaginal hysterectomies increased to 45.5% until 2013 and declined in the following years. Laparoscopic assisted vaginal hysterectomies played only a minor role. The tendency for hysterectomies for endometrial cancer was similar. During the observation period, the share of abdominal hysterectomies fell from 100% to 11.3%, while it increased from 0% to 86.6% for laparoscopic hysterectomies. The other two procedures were less frequently used. Conclusion: Contrary to the German wide decrease of hysterectomies, the amount of hysterectomies at Ulm University Hospital remained constant. However, a clear shift in paradigm regarding the procedures for a hysterectomy took place.